Experimental investigation of raw steel fibers derived from waste tires for sustainable concrete. (3rd March 2023) - Zia, Asad; Zhang, Pu; Holly, Ivan
Highlights: Concrete reinforced with steel fibers recovered from waste tires is investigated. The elastic modulus, linear shrinkage, and water absorption are determined. The strengths and their energy absorptions and toughness indices are reported. Reduction in linear shrinkage is noted. The compressive and split tensile strengths and their energy absorptions improved. Abstract: The increasing pollution burden is a significant hurdle in achieving the United Nations' goals for a sustainable society. Various methods are used to handle pollution, including recycling waste into new products and using waste to improve other materials' properties. In this respect, the trend of using waste materials, especially waste fibers, in the construction industry to improve the strength and durability of concrete is also receiving attention. Currently, most countries use raw steel fibers from waste tires (RSFs) to enhance the properties of cement composites. Using RSFs in construction materials can help decrease pollution and produce low-cost sustainable materials. Therefore, it is essential to explore the suitability of RSFs for enhancing the properties of cement composites. This study aims to explore the suitability of RSFs for durable and sustainable cement composites. The study's specific aim is to evaluate the efficiency of locally available RSFs of Bratislava, Slovakia, for improving local concrete durability and strength properties. For this purpose, the concrete C20/24 of Cemix Bratislava is used. 0.30% to 0.75% of RSFs are added in raw form by volume fraction of the concrete. A statistical analysis of 1057 RSFs is performed to determine the frequencies of their dimensions. The workability of the concrete is measured by using the slump test. The concrete's hardened properties, including compressive strength (CS), split tensile strength (SS), flexure strength (FS), and modulus of elasticity (EM), are evaluated. In addition, water absorption (WA) and linear shrinkage (LS) are also determined. All tests are performed following the ASTM standards except the test for EM. The precrack and postcrack energy absorption and toughness index are also reported for each strength property. The maximum enhancement of 20% and 16% is noted in CS and SS for RSF-incorporated concrete. At the same time, the FS did not improve. The WA increased, and LS decreased for RSFRCs compared to PC. Therefore, it can be concluded that raw steel fibers from discarded tires have the potential to be used for producing sustainable and durable concrete.